Age and Morphological Changes in the Epiponini Wasp Polybia paulista Von Ihering (Hymenoptera: Vespidae) - Garcia, Z. J.; Noll, F. B. [UNESP] (Springer Nature, 2013)
The division of labor is a central theme in the study of social insects. In bees and wasps, this activity is regulated by age polyethism. Important physiological and morphological changes have been widely studied in the polyethism of honeybee workers. In contrast, this is a relatively unexplored subject in social vespids. Our goal was to determine if there are detectable morphological changes in the body of the Epiponini wasp Polybia paulista Von Ihering or in certain glands in relation to age polyethism. We observed changes in the body weight, the salivary gland, and the mandibular gland that were associated with age, and our results suggest that social relationships and task performance are important to these changes. This contrasts with observations in Polistes and is different from the Apis mellifera Linnaeus age polyethism model. © 2013 Sociedade Entomológica do Brasil.
Keywords: Age polyethism; body weight; mandibular gland; neotropical social wasps; salivary gland